Towards an Explanation of the Social Value of Health Systems: An Interpretive Synthesis - Eleanor Beth Whyle; Jill Olivier (Kerman University of Medical Sciences, 2021)
BackgroundHealth systems are complex social systems, and values constitute a central dimension of their complexity. Values are commonly understood as key drivers of health system change, operating across all health systems components and functions. Moreover, health systems are understood to influence and generate social values, presenting an opportunity to harness health systems to build stronger, more cohesive societies. However, there is little investigation (theoretical, conceptual, or empirical) on social values in health policy and systems research (HPSR), particularly regarding the capacity of health systems to influence and generate social values. This study develops an explanatory theory for the 'social value of health systems.' MethodsWe present the results of an interpretive synthesis of HPSR literature on social values, drawing on a qualitative systematic review, focusing on claims about the relationship between 'health systems' and 'social values.' We combined relational claims extracted from the literature under a common framework in order to generate new explanatory theory. ResultsWe identify four mechanisms by which health systems are considered to contribute social value to society: Health systems can: (1) offer a unifying national ideal and build social cohesion, (2) influence and legitimise popular attitudes about rights and entitlements with regard to healthcare and inform citizen's understanding of state responsibilities, (3) strengthen trust in the state and legitimise state authority, and (4) communicate the extent to which the state values various population groups. ConclusionWe conclude that, using a systems-thinking and complex adaptive systems perspective, the above mechanisms can be explained as emergent properties of the dynamic network of values-based connections operating within health systems. We also demonstrate that this theory accounts for how HPSR authors write about the relationship between health systems and social values. Finally, we offer lessons for researchers and policy-makers seeking to bring about values-based change in health systems.